Customary Criminal Liability And The Harm Caused By Perpetrators Of Customary Offenses - Anggraeni, Yustina; Saleh, Mohammad (Journal of Law, Politic and Humanities, 2024)
Customary law is the original law of the Indonesian nation. Every formation of legislation must be based on the values of social justice, one of which is the religious-magical nature of customary law. This research wants to examine customary criminal liability and how to recover losses caused by perpetrators. This research method uses normative juridical research. The results and discussion of this research show that the position of the application of customary sanctions in the national criminal system is recognized as long as it is in accordance with State principles and the formulation of the balance of customary criminal liability must be adjusted to regional characteristics. Where recovery does not only affect bodies or individuals but can also use compensation to carry out certain rituals.